dsRNase1 contribution to dsRNA degradation activity in the Sf9 cells conditioned medium - Koo, Jinmo; Palli, Subba Reddy (Frontiers in Insect Science, 2023)
RNA interference (RNAi) is inefficient in lepidopteran insects, including Spodoptera frugiperda. RNase activity in the lumen and hemocoel is known to contribute to low RNAi efficiency in these insects. Conditioned medium from Sf9 cells developed from ovaries of S. frugiperda shows high dsRNA degradation activity. But the enzymes responsible for this activity have not been identified. The nuclease genes that are highly expressed in Sf9 cells, Rebase, RNaseT2, and dsRNase1, were identified. Knockdown of dsRNase1 in Sf9 cells resulted in a decrease in dsRNA degradation activity in the Sf9 cells conditioned medium. Knockdown of dsRNase1 also increased RNAi efficiency in Sf9 cells. The results from these studies identified a major player in dsRNA degradation activity in the Sf9 cells conditioned medium. We also describe an efficient system that can be used to identify other genes responsible for dsRNA degradation and RNAi efficiency in S9 cells.